Moderating Effect of Ethical Climate between the Relationship of Coach Ethical Leadership and Affective Commitment: An Evidence from Thailand Nonprofessional Soccer Player - Mochammad Fahlevi; Kittisak Jermsittiparsert; Navaporn Wongsuwan; Mohammed Aljuaid; Thitinan Chankoson (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
A multitude of ethical dilemmas perpetually besets non-professional soccer. It is believed that coaches can be beneficial in preventing unethical behavior. Therefore, this study examines the moderating effect of perceived ethical climate on the relationship between coach ethical leadership and the affective commitment of non-professional soccer players. A convenient sampling technique was utilized to collect data from 300 amateur Thai soccer players for this purpose. The Structural Equation Modeling (SEM) demonstrated that the direct effect of player-perceived coach ethical leadership and player-perceived ethical climate has a significant and positive relationship with affective commitment. The indirect impact of the critical findings indicates that players' perceptions of the ethical environment moderate the relationship between their perceptions of the ethical leadership of their coaches and their affective commitment. These findings suggest that ethical climate is integral because it significantly mediates exogenous and endogenous variables. Therefore, this moderating effect relationship is a significant contribution to the study. This study could assist athletes and clubs in understanding the significance of coaching ethical leadership and ethical climate in enhancing the affective commitment of non-professional athletes.